Editorial Vol.XI - Sharma, Om (Economic Literature, 2016)
Editorial board has pleasure to release this issue of Economic Literature, an annual Journal of Department of Economics, Prithvi Narayan Campus, Tribhuvan University, Pokhara (Volume XI, No. 1, June 2013). Through the publication of this journal Department of Economics has been making efforts to promote the general advancement of economic knowledge, information and techniques of analysis since 1981. Our aim is to continue this tradition by publishing highly academic and policy oriented research papers and to provide platforms for enthusiastic scholars who like to publish their scholarly and analytical paper based on fresh research on the issues of interest around the discipline of economics. This issue incorporates analytical articles of contemporary issues of economy ranging from impact of public expenditure, natural resource use, micro-insurance, tourism trends, food security, recreational demand to impact of global recession. Editorial board strongly believe that University Departments should engage in research and disseminate the ideas and findings to the scientific community for the enlightenment of knowledge, not just to deliver the existing knowledge in class rooms; it will not only enrich field of knowledge but also inspire the fresh graduates towards the culture of scientific research and thoughtful writings. If this publication contributed something to strengthen the culture, we will feel great satisfaction. It is, however, up to the reader to evaluate our endeavour. It was not possible to offer this volume to the esteemed readers without the contributions of the authors of articles included in this issue. The board, therefore, reverentially acknowledge the authors who have contributed to the journal. We would also like to thank to those who have assisted us in the course of this publication. Special thanks go to the campus administration for encouragement and support in various ways. The editorial board welcomes all the noble thoughts, constructive comments an